2021
DOI: 10.1371/journal.pone.0255690
|View full text |Cite
|
Sign up to set email alerts
|

Robotic RNA extraction for SARS-CoV-2 surveillance using saliva samples

Abstract: Saliva is an attractive specimen type for asymptomatic surveillance of COVID-19 in large populations due to its ease of collection and its demonstrated utility for detecting RNA from SARS-CoV-2. Multiple saliva-based viral detection protocols use a direct-to-RT-qPCR approach that eliminates nucleic acid extraction but can reduce viral RNA detection sensitivity. To improve test sensitivity while maintaining speed, we developed a robotic nucleic acid extraction method for detecting SARS-CoV-2 RNA in saliva sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Traditionally, upper respiratory swabs have been considered a better specimen for SARS-CoV-2 detection. 8 , 10 , 11 , 15 , 19 , 25 , 28 Meta-analyses have shown that the sensitivity of NP swab is approximately 98%, higher than the sensitivity of saliva. 38 , 40 In our study, however, the sensitivity of upper respiratory swab was 83.7% for AN in the University cohort and 75.8% for NP/OP in hospitalized patients, lower than the sensitivity of saliva in both populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditionally, upper respiratory swabs have been considered a better specimen for SARS-CoV-2 detection. 8 , 10 , 11 , 15 , 19 , 25 , 28 Meta-analyses have shown that the sensitivity of NP swab is approximately 98%, higher than the sensitivity of saliva. 38 , 40 In our study, however, the sensitivity of upper respiratory swab was 83.7% for AN in the University cohort and 75.8% for NP/OP in hospitalized patients, lower than the sensitivity of saliva in both populations.…”
Section: Discussionmentioning
confidence: 99%
“…The reported clinical sensitivity of saliva compared to NP swab ranges widely from 60.7% to 100%. 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Some studies have reported that saliva has a significantly lower detection rate than swab specimens while others show similar detection rates between the two specimens. 8 , 10 , 11 , 15 , 19 , 25 , 28 , 31 Saliva specimens could generate a false negative result in asymptomatic individuals, when collected later in the disease course in symptomatic patients, or when using testing methods that lack an RNA extraction step.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is not noted in the studies that used POPS examined for this review, this may be a particular issue with this specimen type over oral saliva as the potential mixing with sputum during throat clearing to obtain the specimen could increase its viscosity. This is especially an issue when trying to automate the diagnostic protocol to increase testing speed and capacity, where one study that developed a robotic RNA extraction step noted significant issues in using saliva specimens for this due to the inherent variable nature and viscosity of saliva specimens [76]. In many studies, and indeed in most saliva diagnostic tests that have been granted EUAs by the US FDA, stabilisers and preservatives are added to saliva specimens in order to minimise RNA degradation and thus maximise SARS-CoV-2 detection [16].…”
Section: Main Saliva Specimen Collection Transportation and Storage A...mentioning
confidence: 99%